Pengaruh Image Program Studi Komunikasi dan Penyiaran terhadap Loyalitas Mahasiswa dan Calon Mahasiswa - Manalullaili Manalullaili (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2017)
This research entitled the influence of Islamic Communication and Broadcasting Study Program to students and non students loyalty. It aims to investigate the influence of the two variables. To gain the result, the researcher conduct the research and analyze the data by using simple regression through SPSS calculation. After the analysis has been done, it is obtained that the value of R square is 0.190 or 19%. It shows that, only 19% the image of KPI study program influence the loyalty of students and non students. At the end, the students and non students loyalty towards the study program influences the formulation of the KPI’s image.